Discussing the menstrual cycle in the sports medicine clinic: perspectives of orthopaedic surgeons, physiotherapists, athletes and patients. Issue 1 (2nd January 2023) - O'Loughlin, Emma; Reid, Duncan; Sims, Stacy
ABSTRACT: Recently, there has been a global increase in female-based sports medicine research related to physiological aspects of the menstrual cycle. However, it is unclear whether health professionals and athletes routinely and openly discuss this sometimes-sensitive topic. This study explored different members of the sports medicine community's knowledge, perceptions of, and comfort in discussing the endogenous menstrual cycle. Five semi-structured focus group sessions were conducted with 18 participants (2 orthopaedic surgeons, 9 sports physiotherapists, 3 patients, and 4 athletes) in New Zealand. Reflexive thematic analysis revealed an overarching theme which described the menstrual cycle as 'a pertinent and evolving topic in the sports medicine clinic'. The first theme, 'A dearth of education and discussion has given rise to a perceived lack of menstrual cycle knowledge', reflects the participants' consensus regarding a lack of knowledge of the menstrual cycle. In contrast, 'Different (mismatched) concerns of health professionals and non-health professionals' describes the different groups' differing menstrual cycle-related concerns. The third theme, 'Health professionals have specific strategies to enable comfortable menstrual cycle conversations', describes that the broader sports medicine community does not routinely discuss the menstrual cycle in the clinic. In addition, it describes common barriers to in-clinic menstrual cycle discussions, including athlete and health professional age, gender and culture. Finally, the study describes pragmatic approaches health professionals frequently take to tackle these barriers. This study highlights the importance of developing trust, giving context and being aware of athletes' concerns and sociocultural status when discussing the menstrual cycle in the sports medicine clinic.